O porównywalności nieporównywalnego. Wybrane konsekwencje uprawiania pedagogiki jako nauki humanistycznej lub społecznej = On the comparability of the incomparable. Some consequences of pedagogy as a discipline developed within the paradigms of the humanities and social sciences - Sajdak-Burska, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to provide an insight into the difficulties one faces while comparing scientific disciplines in the context of - suggested by some researchers - differences in their development levels. The difficulty lies in paradigmatic differences between the humanities and social sciences as well as in the disparity between the paradigms and the risk of fundamentalism. Pedagogy developed in the perspective of the humanities or social sciences is a subject of tensions related not only to the variety of paradigms, but also to different methodological approaches in search of the truth. Referring to Ken Wilber`s Integral Theory, the author describes different orientations in research, which allows presentation of some consequences of pedagogy developed within the paradigms of the humanities and social sciences.
Keywords: paradygmat; nauki społeczne; nauki humanistyczne; pedagogika; metodologia; paradigms; social sciences; humanities sciences; pedagogy; methodology